Shallow Geology of the CO2CRC Otway Site: Evidence for Previously Undetected Neotectonic Features?. (July 2017) - Bailey, A.H.E.; Pevzner, R.; Urosevic, M.; Popik, D.; Feitz, A.J.
Abstract: Australia's CO2CRC Otway Site hosts a carbon capture and storage (CCS) demonstration facility that has, to date, injected over 80, 000 tonnes of CO2 into two separate geological reservoirs. The reservoir geology is well understood and the site has been the subject of several seismic investigations, though relatively little is known about the near-surface geology and how potential leaks from the injection wells would migrate, particularly within the Port Campbell Limestone. No shallow core has been taken from relevant petroleum wells or water bores, and although there is extensive exposure in the prominent sea cliffs, these are mostly inaccessible. In order to further define the structure and geology of the Port Campbell Limestone at the Otway site, a high-resolution, shallow focused, 3D seismic survey has recently been conducted. The assessment of the near-surface geology described in this paper was used to assist with planning the survey. Using available data, the Port Campbell Limestone is assessed as a series of laterally continuous intercalated limestone, marl, and marly limestones. Interpretation of three previously acquired 3D seismic surveys using a minimum similarity attribute demonstrates evidence for a shallow, steeply east-dipping fault striking approximately NNW-SSE directly below the Otway site. This is observed from approximately 100 m to 380 m depth below surface, where it appears to die out. In the shallow section, the fault is undetectable primarily due to low seismic resolution, and so it is unknown how shallow it propagates. Extrapolation of the fault to the surface projects to between the wells Naylor-1 and CRC-1. A recently acquired high-resolution 3D seismic survey over the study area will allow for this fault to be further delineated.